Ex Vivo Liver Resection and Autotransplantation as Surgical Option for Zone II–III Leiomyosarcoma of IVC: A Case Report and Literature Review - Tuxun, Tuerhongjiang; Li, Tao; Apaer, Shadike; He, Yi-Biao; Bai, Lei; Gu, Shen-Sen; Wang, Zhi-Peng; Huo, Qiang; Wang, Jiang; Zhao, Jin-Ming (Frontiers in Oncology, 2021)
We report the first documented case of leiomyosarcoma at zone II-III of inferior vena cava with thrombi in three hepatic veins undergoing ex vivo liver resection and autotransplantation (ELRA) and hepatic veins thrombectomy. A 33-year-old female patient presented with abdominal distention and lower extremities edema. Abdominal wall varicosis and shifting dullness were positive on physical examination. Her liver function was classified as Child-Pugh B and a solid tumor at retro-hepatic vena cava extending to right atrium with thrombi in three hepatic veins were confirmed. The diagnosis of leiomyosarcoma with Budd-Chiari syndrome was highly suspected with preoperative ultrasound, echocardiogram, CT scan, and three-dimensional reconstruction. A zone II-III leiomyosarcoma of IVC origin was confirmed at surgery and ex vivo liver resection and autotransplantation, and hepatic vein thrombectomy with atrial reconstruction were performed under cardiopulmonary bypass (CPB). Operative time, anhepatic time, and CPB time were 12 h, 128 min, and 84 min, respectively. The patients experienced post-operative liver dysfunction and was cured with conservative therapy. Hepatic recurrence two years after surgery was managed with radiofrequency. The patient was alive with liver metastasis three years after surgery. Despite being regarded as an extremely aggressive procedure, ELRA could be considered in the treatment of advanced leiomyosarcoma with Budd-Chiari syndrome and hepatic vein thrombi.